Quality of Life and Its Related Factors in Adolescents with Epilepsy - Masrour Roudsari D; Chehrehgosha M; Seyyedolshohadayee M; Hosseini AF (Iran University of Medical Sciences, 2011)
Background & Aims: Many children and adolescents with epilepsy live in Iran. This disease affects their quality of life and their social performance. Accordingly this study aims to determine the quality of life of adolescents with epilepsy and its related factors.   Material & Methods: It was a descriptive cross- sectional study. One hundred and eighty 11-20 years old adolescents referring to Iran epilepsy society and Loghman-e- Hakim hospital were recruited by continuous sampling during a four months period. Data was collected by QOLIEZ- AD- 48 and Analyzed using SPSS-PC (v.16).   Results: Total score of Quality of life was (43/97 ± 11/58). The highest score was related to school performance (80/79 ± 18/09) and the lowest score was related to attitude towards epilepsy (15/65 ± 15/76).Among the studied factors, the number of epileptic seizures (p=0.002) and the last time of experiencing seizure (p<0.001) had significant association with quality of life. There was also a significant relationship between ethnicity (p=0.042), the place of residency (p=0.032), adolescents' education (p=0.001), mother's education (p=0.002), income (p=0.001), number of children (p<0.001), awareness of peer group (p=0.006) and quality of life.   Conclusion: Considering the level of quality of life and its related factors is recommended in caring about these adolescents in the community.